Ethical issues surrounding the use of assisted reproductive technologies in Ghana: An analysis of the experiences of clients and service providers - Rosemond Akpene Hiadzi; Bryan Woodward; Godwin Banafo Akrong (Heliyon, 2023)
Since the advent of Assisted Reproductive Technologies (ART) in Ghana about three decades ago, IVF and ICSI treatments have enabled infertile Ghanaian couples to fulfill their aspirations and dreams of having children. In this extremely pronatalist society, ART has provided relief to many childless couples by reducing, if not eliminating, the shame of childlessness that they would otherwise have to suffer. However, as the provision and utilization of ART continue to increase, so do worries regarding the ethical difficulties surrounding this field of medicine, which challenge cultural ideals and personal desires. The study explores client and service provider experiences with ART in urban Ghana. Observation and in-depth interviews were employed to collect data, and the ethical dimensions of people's experiences relative to Ghanaian cultural and ethical values were analyzed. The results show that the provision of ART services for heterosexual couples in marital unions, the availability of PGT for sickle cell clients, the preference for multiple births emerging from embryo transfers, the lower preference for cryopreservation, the high cost of ART treatment, and the need for regulation of the provision of ART services in Ghana were some of the ethical concerns expressed by both clients and service providers.